Applicability of HIN-1, MGMT and RASSF1A promoter methylation as biomarkers for detecting field cancerization in breast cancer. Issue 1 (December 2015) - Spitzwieser, Melanie; Holzweber, Elisabeth; Pfeiler, Georg; Hacker, Stefan; Cichna-Markl, Margit
Abstract Introduction It has been shown in some articles that genetic and epigenetic abnormalities cannot only be found in tumor tissues but also in adjacent regions that appear histologically normal. This phenomenon is metaphorically called field cancerization or field defect. Field cancerization is regarded as clinically significant because it is assumed to be an important factor in local recurrence of cancer. As the field showing these molecular abnormalities may not be removed completely by surgery, these changes might lead to neoplasms and subsequent transformation to a tumor. We aimed to investigate the applicability of the methylation status of six tumor suppressor genes as biomarkers for detecting field cancerization in breast cancer. Methods The promoter methylation status ofCCND2, DAPK1, GSTP1, HIN-1, MGMT andRASSF1A was determined by methylation-sensitive high-resolution melting (MS-HRM) analysis. MS-HRM methods forCCND2, MGMT andRASSF1A were developed in-house, primer sequences forDAPK1, GSTP1 andHIN-1 have already been published. Biopsy samples were taken from tumor, tumor-adjacent and tumor-distant tissue from 17 breast cancer patients. Normal breast tissues of four healthy women served as controls. Results All MS-HRM methods proved to be very sensitive. LODs were in the range from 0.1 to 1.5 %, LOQs ranged from 0.3 to 5.3 %. A total of 94 %, 82 % and 65 % of the tumors showed methylation ofRASSF1A, HIN-1 and MGMT promoters, respectively. The methylation status of these promoters was significantly lower in tumor-distant tissues than in tumor tissues. Tumor-adjacent tissues showed higher methylation status ofRASSF1A, HIN-1 andMGMT promoters than tumor-distant tissues, indicating field cancerization. The methylation status of theHIN-1 promoter in tumor-adjacent tissues was found to correlate strongly with that in the corresponding tumors (r = 0.785, p < 0.001), but not with that in the corresponding tumor-distant tissues (r = 0.312, p = 0.239). Conclusions Among the gene promoters investigated, the methylation status of theHIN-1 promoter can be considered the best suitable biomarker for detecting field cancerization. Further investigation is needed to test whether it can be used for defining surgical margins in order to prevent future recurrence of breast cancer.